Applying reduced impact logging to advance sustainable forest management: international conference proceedings 26 February to 1 March 2001, Kuching, Malaysia - Enters, T.; Durst, P.B.; Applegate, G.; Kho, P.C.S.; Man, G. (Food and Agriculture Organization of the United Nations, 2002)
In tropical forests, RIL has been tested and appliedon a small scale for more than a decade. Various timber-producing countries in Asia and the Pacific have recognized its potential for advancing sustainable forest management. Yet many questions remain and the lack of sound and appropriate information continues to impede the widespread application of RIL. This book helps fill that critical information gap. It includes a wealth of information that was presented during the International conference on the application of reduced impact logging to advance sustainable forest management, 26 February to 1 March 2001, Kuching, Malaysia. The conference assessed past and ongoing efforts to implement RIL and considered options for future application. It reflects an important milestone in the efforts to improve forest management in the region. While acknowledging that considerable challenges lie ahead, it provides reason for cautious optimism concerning the wider application of RIL in the future.